Evolution of the Gelasian (Pleistocene) slope turbidite systems of southern Marche (Peri-Adriatic basin, central Italy). Issue 1 (1st January 2016) - Di Celma, Claudio; Teloni, Riccardo; Rustichelli, Andrea
Abstract : Examples of slope channels and canyons being diverted by structurally related sea-floor topography are commonly found both on the modern seabed and in the subsurface, in deep-water fold and thrust belts but their depositional histories have rarely been documented using examples from outcrop. The synthesis of outcrop (original geological field mapping at 1:10, 000 scale) and subsurface data sets from the early Pleistocene stratigraphic succession of the Peri-Adriatic basin provides a window into the overall evolutionary pattern of large intraslope turbidite systems that, during the Gelasian (2.58–1.80 Ma), shed Apennine-derived clastic sediments into the adjacent deep-water basin. Trends from mapping and paleocurrent indicators converge to indicate that the sea-floor bathymetric expression of a thrust-related anticline, the north-trending Jesi-Nereto-Zaccheo structure, likely influenced the downslope transport direction of gravity flows and sediment dispersal pattern. During early and middle Gelasian time, coarse-grained turbidite deposition occurred on the western flank of the intraslope anticline by westerly sourced, northward-flowing turbidity currents, indicating that the opposing sea-floor topography was sufficient to cause the diversion of turbidite systems, forcing them to travel near parallel to the east-facing regional paleoslope for significant distances. By very late Gelasian time, the intraslope accommodation space on the western flank of the anticline had filled and turbidites were dispersed through dip-oriented conduits incising across the crest of the underlying structure.